Impact of pulses, starches and meat on vitamin D and K postprandial responses in mice. (15th February 2023) - Antoine, Tiffany; El Aoud, Asma; Alvarado-Ramos, Katherine; Halimi, Charlotte; Vairo, Donato; Georgé, Stéphane; Reboul, Emmanuelle
Highlights: Chickpeas reduce vitamin D and K postprandial responses in mice compared to potatoes. Meat reduces vitamin D and K postprandial responses in mice compared to potatoes. Semolina did not impair vitamin postprandial responses in mice compared to potatoes. Chickpeas and meat reduce vitamin D/K intestinal content in mice compared to potatoes. Abstract: In vitro experiments showed that i) phytates, tannins and saponins from pulses can alter vitamin D and K bioavailability and ii) meat decreased vitamin D bioaccessibility by impairing its stability during digestion. We aimed to confirm these results in vivo by force-feeding mice with emulsions containing either potatoes or semolina or chickpeas or meat. Vitamin D and K plasma responses decreased after a gavage with chickpeas or meat compared with potatoes (−62 % and −67 %, respectively for vitamin D, −40 % and −64 %, respectively for vitamin K; p < 0.05). Vitamin D and K intestinal contents were also reduced in mice force-fed with chickpeas or meat compared with potatoes (from −64 to −83 % and from −76 to −84 %, respectively for vitamin D and from −7 to −59 % and from −7 to −90 %, respectively for vitamin K; p < 0.05). The results confirm that chickpea and meat compounds can decrease vitamin D and K bioavailability.